2024
DOI: 10.1038/s41598-024-53080-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific enolase at admission as a predictor for stroke volume, severity and outcome in ischemic stroke patients: a prognostic biomarker review

Matheus Menão Mochetti,
Estêvão Garcia Porello Silva,
Adriana Aparecida Feltrin Correa
et al.

Abstract: An ideal blood biomarker for stroke should provide reliable results, enable fast diagnosis, and be readily accessible for practical use. Neuron-specific enolase (NSE), an enzyme released after neuronal damage, has been studied as a marker for brain injury, including cerebral infarction. However, different methodologies and limited sample sizes have restricted the applicability of any potential findings. This work aims to determine whether NSE levels at Emergency Department (ED) admission correlate with stroke … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Studies have shown that serum NSE levels are positively correlated with the size of cerebral infarction and promote local neuroinflammatory response, which is an indicator to judge the severity of brain injury ( 41 ). Recent studies have shown that NSE is closely related to stroke prognosis and is a reliable indicator of stroke functional prognosis ( 42 ). The level of serum NSE is a sensitive biochemical index for judging the degree of brain nerve damage in patients with vascular dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that serum NSE levels are positively correlated with the size of cerebral infarction and promote local neuroinflammatory response, which is an indicator to judge the severity of brain injury ( 41 ). Recent studies have shown that NSE is closely related to stroke prognosis and is a reliable indicator of stroke functional prognosis ( 42 ). The level of serum NSE is a sensitive biochemical index for judging the degree of brain nerve damage in patients with vascular dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that measuring NSE concentrations in biological fluids such as serum and cerebrospinal fluid (CSF) is clinically relevant [13][14][15][16]. Serum NSE levels are higher in patients with ischemic stroke than in healthy controls and correlate with infarct size and neurological deficits [17,18].…”
Section: Introductionmentioning
confidence: 99%